2017
DOI: 10.1039/c7ob01198a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing a long-range salt bridge with intermediate aromatic and nonpolar amino acids

Abstract: The interaction of a positively charged amino acid residue with a negatively charged residue (i.e. a salt bridge) can contribute substantially to protein conformational stability, especially when two ionic groups are in close proximity. At longer distances, this stabilizing effect tends to drop off precipitously. However, several lines of evidence suggest that salt-bridge interaction could persist at longer distances if an aromatic amino acid residue were positioned between the anion and cation. Here we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…The obtained X-ray crystal structure of R288H apo (PDB ID: 7E2O) and WT apo (PDB ID: 2ZK0) 9) were compared (Figs. 3a-d, f) and showed that Arg288 and Glu295 formed a long-range salt bridge [13][14][15][16][17][18][19][20][21] in WT (Fig. 3b).…”
Section: Resultsmentioning
confidence: 92%
“…The obtained X-ray crystal structure of R288H apo (PDB ID: 7E2O) and WT apo (PDB ID: 2ZK0) 9) were compared (Figs. 3a-d, f) and showed that Arg288 and Glu295 formed a long-range salt bridge [13][14][15][16][17][18][19][20][21] in WT (Fig. 3b).…”
Section: Resultsmentioning
confidence: 92%
“…Solid-Phase Synthesis: General probe synthesis procedures were adapted from those of Mason Smith based on his previous work in peptide synthesis (Smith, Billings et al 2017).…”
Section: Probe Synthesis and Purificationmentioning
confidence: 99%
“…The fiber orientation distribution within an undeformed ROI (i.e. region between a pair of consecutive photobleach stripes) of a fascicle and ROI strain were used to predict the fiber orientation distribution of respective deformed configuration of the ROI assuming affine deformation by using following relation (Smith, Billings et al 2017).…”
Section: Evaluation Of Collagen Fiber Deformation Behavior and Degradation Dependentmentioning
confidence: 99%
“…However, the formation of a salt bridge was suggested through the interaction of a positively charged amino acid with a negatively charged one, potentially contributing to protein conformational stability, especially when these two ionic groups are located adjacent to each other [22]. In addition, the aliphatic index of CGT-BS indicates a higher value and showed a close similitude to other selected CGTases proteins, hence indicating thermally stable CGTase proteins.…”
Section: Prediction Of Theoretical Physicochemical Properties Of β-Cyclodextrin Glycosyltransferase (Cgt-bs)mentioning
confidence: 99%